Chemical composition and hepatoprotective effect of essential oil from Myrtus communis L. flowers against CCL4-induced acute hepatotoxicity in rats. Issue 7 (28th January 2019) - Ben Hsouna, Anis; Dhibi, Sabah; Dhifi, Wissal; Mnif, Wissem; Ben Nasr, hmed; Hfaiedh, Najla
Abstract : Myrtus communis  L. (Myrtle) is one of the most important aromatic and medicinal species from the Myrtaceae family. Abstract : Myrtus communis L. (Myrtle) is one of the most important aromatic and medicinal species from the Myrtaceae family. It is traditionally used as antiseptic, disinfectant drug and hypoglycemic agent. The aim of our study was to evaluate the protective effect of Myrtus communis essential oil ( Mc EO) on CCl4 -induced hepatotoxicity in rat. Thirty two adult Wistar rats were divided into 4 groups of 8 each: (1) a control group; (2) was given a single dose of CCl4 (1 mL kg −1 in 1% olive oil. ip) on the 14 th day (3) were given during 15 days a daily i.p. injection of Mc EO at 250 mL kg −1 b.w (4) a group was pretreated with Mc EO and intoxicated with CCl4 on the 14 th day. The major components of Mc EO are α-pinene (35.20%), 1, 8-cineole (17%), linalool (6.17%) and limonene (8.94%) which accounted for 67.31% of the whole oil. The antioxidant activity of Mc EO was evaluated using DPPH scavenging ability, β-carotene bleaching inhibition and hydroxyl radical-scavenging activity. Moreover, the effect of Mc EO (250 mg kg −1 body weight BW) administrated for 14 consecutive days was evaluated in wistar rat. Administration of a single dose of CCl4 caused hepatotoxicity as monitored by an increase in lipid peroxidation (thiobarbituric acid reactive substances) as well in protein carbonyl level but decreased in antioxidant markers in the liver tissue. The Mc EO pre-treatment significantly prevented the increased plasma levels of hepatic markers and lipid levels induced by CCl4 in rats. Furthermore, this fraction improved biochemical and histological parameters as compared to CCl4 -treated group. Our results suggest that M. communis contains promising substances to counteract the CCl4 intoxication and which may be efficient in the prevention of hepatotoxicity complications.